Phytoremediation of DEHP and heavy metals co-contaminated soil by rice assisted with a PGPR consortium: Insights into the regulation of ion homeostasis, improvement of photosynthesis and enrichment of beneficial bacteria in rhizosphere soil. (1st December 2022) - Liu, Anran; Wang, Wenjing; Chen, Xiancao; Zheng, Xiaoyan; Fu, Wenting; Wang, Gang; Ji, Jing; Guan, Chunfeng
Abstract: The coexistence of di (2-ethylhexyl) phthalate (DEHP), Cd, and Zn poses a serious challenge to soil ecosystems. This study aimed to evaluate the phytoremediation potential of rice assisted with a plant growth promoting rhizobacteria (PGPR) consortium for the remediation of DEHP, Cd, and Zn co-contaminated soil. The consortium consisted of four bacterial strains, all of which exhibited Cd–Zn resistance and DEHP degradability. The results showed that the rice assisted by the bacterial consortium dissipated 86.1% DEHP while removing 76.0% Cd 2+ and 92.2% Zn 2+ from soil within 30 d. The presence of the PGPR consortium promoted plant growth and improved soil enzymatic activity, which may have helped enhance the removal of DEHP and heavy metals from the soil. Moreover, the application of the consortium modified the bacterial community and increased the relative abundance of bacteria related to DEHP degradation ( Sphingomonas, Xanthobacteraceae), heavy metal immobilization ( Massilia ), and soil nutrient cycling ( Nitrospira, Vicinamibacterales), which promoted plant growth and the removal of DEHP and heavy metals from soil. Notably, the DEHP and heavy metal contents in rice decreased substantially during the phytoremediation process. Therefore, the PGPR consortium could be beneficial for enhancing the removal of DEHP and heavy metals from the soil, without inducing the accumulation of these pollutants in rice. In general, this study confirmed that the combined use of rice and the PGPR consortium could remedy DEHP and heavy metal co-contaminated soil economically and ecologically without simultaneously posing risks for rice consumption. Graphical abstract: Image 1 Highlights: A PGPR consortium with Cd–Zn resistance and DEHP degradability was established. PGPR consortium inoculation improved the remediation of DEHP, Cd and Zn. The inoculation of PGPR consortium decreased the content of pollutants in rice. PGPR consortium regulated rice ion homeostasis and enhanced rice photosynthesis. PGPR consortium increased the relative abundance of beneficial bacteria in soil.